2023
DOI: 10.1002/cbdv.202200982
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Oxidative Stress, Apoptosis, Endoplasmic Reticulum Stress and Autophagy Pathways to the Ameliorative Effects of Hesperidin in NaF‐Induced Testicular Toxicity

Abstract: The ameliorative effects of hesperidin (HES) on the toxicities created by sodium fluoride (NaF) in the testes tissue of rats were studied via oxidative stress, apoptosis and endoplasmic reticulum (ER) stress pathways. The animals were divided into five distinct groups (7 rats in each group). Group 1 was control group, group 2 received NaF-only (600 ppm), group 3 received HES-only (200 mg/kg bw); group 4 received NaF (600 ppm) + HES (100 mg/kg bw) and group 5 received NaF (600 ppm) + HES (200 mg/kg bw) for 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…35 Moreover, the anticancer effects of certain cancer drugs, such as cisplatin, 36 38 Prior research has demonstrated antioxidant effectiveness in preventing cancer cell growth and their roles in apoptosis. 39,40 With this idea, we addressed the molecular bases of CAPE-induced apoptosis by first evaluating possible changes in ROS levels and ΔΨM. ROS serve as precursors that trigger antioxidant response elements, 24 and previous studies have linked CAPE exposure to ROS formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Moreover, the anticancer effects of certain cancer drugs, such as cisplatin, 36 38 Prior research has demonstrated antioxidant effectiveness in preventing cancer cell growth and their roles in apoptosis. 39,40 With this idea, we addressed the molecular bases of CAPE-induced apoptosis by first evaluating possible changes in ROS levels and ΔΨM. ROS serve as precursors that trigger antioxidant response elements, 24 and previous studies have linked CAPE exposure to ROS formation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although anticancer therapy‐induced apoptosis might eradicate cancer cells, sublethal activation of caspase 3 may cause neoplastic development because inadequate apoptosis induction can activate survival mechanisms like autophagy 38 . Prior research has demonstrated antioxidant effectiveness in preventing cancer cell growth and their roles in apoptosis 39,40 . With this idea, we addressed the molecular bases of CAPE‐induced apoptosis by first evaluating possible changes in ROS levels and ΔΨM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 78 ] In case of an imbalance in the Bax/Bcl‐2 ratio, p53 may further increase the amount of cytochrome c released into the cytoplasm by changing the level of Bcl‐2 family proteins. [ 79 ] Cytochrome c, which passes into the stasis, binds to APAF‐1 and activates Caspase‐9. Subsequently, Caspase‐9 activates Caspase‐3 as an apoptotic factor.…”
Section: Discussionmentioning
confidence: 99%
“…They can be proteins or peptides secreted by different cell types, including immune cells, in response to diverse stimuli such as infections, injuries, or immune responses. Examples of cytokines encompass interleukins (IL-2, IL-6, IL-8, IL-12), TNF-α, and IFNs [ 43 , 44 , 45 ]. TNF-α participates in the destruction of tumor cell structure and the induction of cell apoptosis and may serve as a co-stimulatory factor for mitogen-activated normal B cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%